Il diritto ecclesiastico italiano e le minoranze religiose negli anni del confessionismo - Tira, Alessandro (2022)
Religious minorities and the Italian law in the age of confessionalism · In the 1930s-1950s, the Italian system of law and religion maintained the same features, despite a new Constitution was enforced in 1948. For the entire period, religious minorities were basically regulated by the Admitted Denominations Act 1929 and the application of such rules was inspired by the entrenched confessionalism of public institutions. The essay considers the main features of that legislation, some of the early efforts to reform it and the approach to the whole matter during the 1950s.
Keywords: Religious Minorities; Italian Law; Italian Constitution; Confessionalism